MOTOR BEHAVIOR IN MOTHER-INFANT INTERACTION (Fiep Bulletin - online, 2015)
Human development has been investigated with its different early social interaction components. However, motor behavior has been neglected despite its importance for mutual regulation between mother and infant during interaction. The present article discusses the theoretic basis of the importance of the infant motor behavior in the interaction with the mother, assuming the motor behavior development as socially mediated. Infant motor behaviors participate and influence the interactions and are reciprocally constructed and stimulated by them.
Keywords: .